2017
DOI: 10.1007/s11764-017-0655-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for earlier return to work of cancer patients

Abstract: PurposeThis study aims to investigate how perceived work ability, job self-efficacy, value of work, and fatigue predict return to work (RTW) in cancer patients who received chemotherapy.MethodsData of a before-after study on a multidisciplinary intervention that aimed to enhance RTW was used, consisting of four assessments up to 18 months. Time to partial and full RTW of 76 and 81 participants, respectively, was analyzed in Cox proportional hazard analysis with time-dependent variables. Univariate analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
3
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 35 publications
7
69
3
9
Order By: Relevance
“…It was the most frequently self‐reported reason for impaired RTW, and fatigue persisting 1.5 years after end of therapy was a significant determinant for impaired RTW in the long run. Our results strengthen findings from previous trials that also found an influence of fatigue on RTW (Kiasuwa Mbengi et al, ; Mehnert, ; Porro et al, ; Wolvers, Leensen, Groeneveld, Frings‐Dresen, & Boer, ). Thus, health professionals' and the public's awareness needs to be raised that fatigue is a serious syndrome (and not just listlessness or moaning) that severely hampers general functioning and daily routine.…”
Section: Discussionsupporting
confidence: 91%
“…It was the most frequently self‐reported reason for impaired RTW, and fatigue persisting 1.5 years after end of therapy was a significant determinant for impaired RTW in the long run. Our results strengthen findings from previous trials that also found an influence of fatigue on RTW (Kiasuwa Mbengi et al, ; Mehnert, ; Porro et al, ; Wolvers, Leensen, Groeneveld, Frings‐Dresen, & Boer, ). Thus, health professionals' and the public's awareness needs to be raised that fatigue is a serious syndrome (and not just listlessness or moaning) that severely hampers general functioning and daily routine.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to the present study, Wolvers et al [29] found RTWSE to be predictive of RTW in employees with cancer. Keeping in mind that the participants in Wolver et al's study [29] were all in curative treatment, in physically good shape, and motivated for RTW, one might speculate that RTWSE is more likely to be predictive of RTW in populations of cancer patients in curative care who are motivated for RTW than in populations of cancer patients with a wider range of treatment intentions (i.e., curative, adjuvant, neo-adjuvant and palliative) who are therefore potentially less motivated for RTW. It is well-known that after being diagnosed with a life-threatening illness, life priorities may change [12][13][14], and it is possible that a subsample in the present study could have had an expectation of being able to RTW but chose not to RTW due to other life priorities.…”
Section: Interpretation Of Findings and Implicationscontrasting
confidence: 99%
“…Likewise, the employees undergoing palliative treatment may also have had other life priorities beside RTW [13,14,49,50]. Differences in sample characteristics with regard to treatment intention and motivation for RTW are therefore possible explanations as to why RTWSE failed to predict RTW in the present sample of employees with cancer but was predictive in the study by Wolvers et al [29]. The majority of the population in Wolvers et al's study was women with breast cancer, too.…”
Section: Interpretation Of Findings and Implicationsmentioning
confidence: 64%
See 2 more Smart Citations